Pengaruh Stimulasi Oral Terhadap Kemampuan Menghisap Pada Bayi Prematur di RSUD Dr. Moewardi Surakarta - Ramadhani, Alinda Nur; , Agus Widodo, S.Fis., M.Fis; , Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: sucking and swallowing mechanism is not well developed in preterm infants. This sucking weakness associated with the maturity of the baby's nervous structure and strength of the muscles of the mouth. Less matures sucking development in preterm infants is characterized by the emergence of oral feeding problems that would cause delays in breastfeeding, low weight and dehydration during the early weeks after birth. Oral stimulation program is one of the interventions used to enhance the sucking ability in preterm infants. Objective: To determine the effect of oral stimulation on the sucking ability in preterm infants. Method: The study was a descriptive analytic with one group pre and post test design, which uses only one treatment group with no control group. Samples in the treatment group was given oral stimulation with a duration of 15 minutes with the frequency of 1 times each day for 1 week. Measurement of the sucking ability done by measuring how much milk can be drunk (ml) every once drinking, frequency of drinking milk in one day and changes in body weight (grams). The data analysis was made in the form of descriptive data, which is the form of the amount of milk that can be taken (ml) per day will be measured using a bottle measured in milliliters (ml) and are presented in graphical form the results of pre and post test for each sample. Another outcome is weight change (grams) was measured using scales weight (grams) and are presented in graphical form of pre and post test results for each sample. Result: There was an effect of oral stimulation on the sucking ability in preterm infants seen from the increase in the volume of milk consumed, increase in the frequency of milk drinking and increase in weight gain. Conclusion: There was an effect of oral stimulation on the sucking ability in preterm infants. Keywords: oral stimulation, sucking ability, preterm infants.